O papel da via de sinalização p38 MAPK no desenvolvimento do Schistosoma mansoni (Platyhelminthes:Trematoda) e na proteção contra o estresse oxidativo - Lívia das Graças Amaral Avelar (2013)
There are three important Schistosoma species parasitizing humans: Schistosoma mansoni, S. japonicum and S. haematobium. Together, they are responsible for the chronic infection of 200 million people and over 200,000 annual deaths worldwide. The only drug to treat schistosomiasis is Praziquantel® (PZQ) that has been used for over 40 years. Although PZQ is an efficacious drug, with some limitations, and resistance development is of concern. To contribute to a solution, various information of the recently sequenced genomes of these parasites was used to identify potential targets for the development of an alternative drug. Since eukaryotic protein kinases (ePKs) are good medical targets for drug development in different biological systems, they have become the focus of this study. A signaling pathway studied by our group is to MAPK. Protection against oxidative stress is necessary for S. mansoni homeostasis and regulated in other species by the action of p38 MAPK signaling pathway. Therefore, we propose to assess the role of p38 MAPK signaling pathway in the development of S. mansoni and protection against oxidative stress. Tree main questions drive this work: 1. the p38 MAPK signaling pathway is required for S. mansoni homeostasis? 2. the p38 MAPK signaling pathway is crucial for the parasite survival against oxidative stress? 3. which target genes of p38 MAPK signaling pathway have expression regulated? After a significant reduction in the transcription level by gene silencing of the p38 MAPK, no visible phenotypic changes were reported in schistosomula in culture. Therefore, mice were infected with the silenced or inhibited schistosomula and the development of adult worms was observed. It was showed that p38 MAPK has an important role in transformation and survival of the parasites as low number of adult worms was recovered, the egg production was significantly lower, the tegument of survived worms was damaged, and female worms had underdeveloped ovaries. Furthermore, only ≈ 13% of the eggs produced develop into mature eggs. Our results suggest that inhibition of the p38 MAPK activity interfere in protecting parasites against reactive oxygen species and also demonstrate that p38 MAPK and glutamate-cysteine-ligase are overexpressed in parasites after exposition to oxidative stresses. Together our data show that p38 MAPK signaling pathway is a critically important route and may represent an attractive therapeutic target for the treatment and control of schistosomiasis.